2021
DOI: 10.1038/s41598-021-97424-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynapenia is highly prevalent in older patients with advanced idiopathic pulmonary fibrosis

Abstract: Body composition and muscle strength are emerging aspects in idiopathic pulmonary fibrosis (IPF) clinical assessment. We aimed to study the relationships of handgrip strength (HGS) with anthropometric variables, body composition, and disease staging, and to evaluate the prevalence of dynapenia in 102 clinically stable IPF patients (70 M; mean age: 69.4 years). Fat-free mass (FFM), skeletal muscle (SM) were estimated with bioimpedance analysis. HGS was measured with a digital handle dynamometer for both dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
3
5
1
Order By: Relevance
“…A recent study by Hanada et al applied the diagnostic criteria of the Asian Working Group for Sarcopenia 2019 in a cohort of 78 patients with interstitial lung diseases (ILD) of Asian ethnicity and observed a prevalence of sarcopenia of 32%, higher than the one we observed in our cohort of patients with IPF at diagnosis [12]; however, these differences may be due to the different ethnicity of the study population (in our study all patients were Caucasian) and to the different underlying pulmonary disease. On the contrary, Bocchino et al in a cohort of Italian patients with IPF at various stages of the disease reported a prevalence of dynapenia defined in accordance to the EWGSOP2 criteria (hand grip < 27 kg for men and < 16 kg for women) exactly comparable to ours (22.9 and 21.6% in our cohort at disease diagnosis and at 6-month follow-up, respectively, and 23.5% in the cohort by Bocchino et al) [13]. Furthermore, similarly to our study, Bocchino et al observed an association between disease severity and dynapenia, and Guler et al observed that ILD severity impacted on both grip strength, gait speed and body composition [13,14].…”
supporting
confidence: 74%
See 3 more Smart Citations
“…A recent study by Hanada et al applied the diagnostic criteria of the Asian Working Group for Sarcopenia 2019 in a cohort of 78 patients with interstitial lung diseases (ILD) of Asian ethnicity and observed a prevalence of sarcopenia of 32%, higher than the one we observed in our cohort of patients with IPF at diagnosis [12]; however, these differences may be due to the different ethnicity of the study population (in our study all patients were Caucasian) and to the different underlying pulmonary disease. On the contrary, Bocchino et al in a cohort of Italian patients with IPF at various stages of the disease reported a prevalence of dynapenia defined in accordance to the EWGSOP2 criteria (hand grip < 27 kg for men and < 16 kg for women) exactly comparable to ours (22.9 and 21.6% in our cohort at disease diagnosis and at 6-month follow-up, respectively, and 23.5% in the cohort by Bocchino et al) [13]. Furthermore, similarly to our study, Bocchino et al observed an association between disease severity and dynapenia, and Guler et al observed that ILD severity impacted on both grip strength, gait speed and body composition [13,14].…”
supporting
confidence: 74%
“…in a cohort of Italian patients with IPF at various stages of the disease reported a prevalence of dynapenia defined in accordance to the EWGSOP2 criteria (hand grip < 27 kg for men and < 16 kg for women) exactly comparable to ours (22.9 and 21.6% in our cohort at disease diagnosis and at 6-month follow-up, respectively, and 23.5% in the cohort by Bocchino et al . ) [ 13 ] . Furthermore, similarly to our study, Bocchino et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the post-acute COVID-19 patients we studied, HGS was much greater in males compared to females, as already reported (8,54), and lower in older patients. Using the EWGSOP 2019 criteria, the percentage of dynapenic patients was 65% in males and 47% in females; this prevalence is much greater than the one determined by our group in patients with COPD (unpublished data) or idiopathic pulmonary fibrosis (55). HGS was also more strongly correlated with PhA and IRs than BC, confirming that raw BIA variables are potential markers of muscle function.…”
Section: Discussionsupporting
confidence: 45%